Contribution of long-chain fatty acid to induction of myeloid-derived suppressor cell (MDSC)-like cells – induction of MDSC by lipid vesicles (liposome). (1st November 2020) - Yoshida, Yoichiro; Nagamori, Tsunehisa; Ishibazawa, Emi; Kobayashi, Hiroya; Kure, Tomoko; Sakai, Hiromi; Takahashi, Daisuke; Fujihara, Mitsuhiro; Azuma, Hiroshi
Abstract: Context: Effects of liposomal particles on immune function have not been adequately investigated. Earlier reports indicate that intravenous injection of rats with pegylated liposomes comprising chemically defined specific lipids produces myeloid derived suppressor-cell (MDSC)-like cells in the spleen. Objectives: After liposome injection, we sought a cell surface marker expressed specifically on splenic macrophages. Then we assessed the immunosuppressive activity of macrophages positive for the marker. Furthermore, we investigated whether immunosuppression induction is an immunopharmacological action specific to this pegylated liposome, or not. Materials and Methods: After using a microarray system to screen genes enhanced by this liposome, we evaluated cell surface expression of gene products using flow cytometry. Liposomes of several kinds, each comprising one type of phospholipid, were prepared and evaluated for their ability to induce T-cell suppression. Results: Microarray analysis indicated enhanced B7-H3 expression. Flow cytometry revealed that the B7-H3 molecule was expressed on splenic macrophages after liposome injection. B7-H3 + macrophages were positive for iNOS. Removing B7-H3 + cells restored T-cell proliferation. Similarly to this liposome, various liposomes with different long chain fatty acids induced T-cell suppression when accumulated in the spleen. Conclusions: Immunosuppressive cells induced by this pegylated liposome closely resemble MDSCs, especially B7-H3 + MDSCs. Immunosuppression induction is not a phenomenon specific to this liposome. Accumulation of long chain fatty acid in macrophages by internalization of liposomal nanoparticles might be related to macrophage acquisition of immunosuppressive activity in vivo .